Career conversations : how to get the best from your talent pool - Smith, Greg (John Wiley and Sons Australia, Ltd, 2019)
Retain your talent with a proactive approach to employee development, one conversation at a time When employees are happy at work, the energy and creativity they possess is virtually limitless. But many leaders are ill-equipped to discuss and gauge the career satisfaction of their employees, and risk losing their talent to their competitors. Career Conversations is your guide to developing the skills needed for effective career discussions with your staff, providing step-by-step instructions on how to incorporate this capability into your leadership routine. It has never been easier for employees to seek other job opportunities. Search firms and online platforms such as LinkedIn make the danger of the competition poaching your best employees all too real. To take active, dynamic and genuine interest in their employee's career satisfaction and development, leaders require the skills and knowledge to have ongoing career conversations. Packed full of case studies, practical exercises and key insights, career development expert Greg Smith explains how leaders can guide their employees to achieve career satisfaction by taking an active, dynamic and ongoing interest in their development.-engage with employees on career aspirations -listen critically and build trust -help employees reinvent themselves for the future of work -gain self-insight and become a more effective leader -empathise and respond to your staff's needs. Career Conversations is a must-read for current and aspiring organisational leaders, Human Resource directors, HR practitioners, senior executives, supervisors, managers and business owners. This book will help you guide your employees through their careers and, in turn, help your company thrive.